Occupational Hand Eczema among Cement users in Nepal - Sabina Bhattarai; Rohit Murarka; Sumed Mishra; Astha Nepal; Sunil Kumar Joshi (Occupational Health and Safety Society of Nepal, 2017)
Background: Occupational dermatitis among cement workers is a major occupational health concern and skin contact with cement has been associated with contact dermatitis, which ranges from cement burns to cumulative irritant contact dermatitis. Objective: The objective of this study was to investigate the prevalence and severity of occupational cement contact dermatitis amongst cement workers in Nepal which is the first of its kind. Methods: A cross sectional descriptive study amongst patients in construction site and hardware shops within the Kathmandu valley were selected. A structured questionnaire was used to evaluate the demographic data and work-related activities of these cement workers. A complete skin examination was conducted and skin manifestations were assessed by a dermatologist. The data collected was compiled and appropriate statistical tools was used to find out the significance of variables. Result: Out of the total number of workers screened 164/377 (43.50%) had hand contact dermatitis. There were males 148(90.2%) and females16 (9.8%) and the age ranged from 15-51 years ( mean 27.41± 7.68 years).The duration of the disease ranged from 1-360 months (median 36months (IQR=60).The most common site of lesion was palms (62.8%) followed by tip of the fingers in 39.0% patients and the most common morphology of the lesion was erythema seen in 59.1% followed by scaling seen in 51.8 % patients. Conclusion: The issue of contact and irritant hand eczema amongst cement workers in Nepal has had a considerable morbidity. Identification of these patients with adequate treatment, test of the suspected allergens and counseling could further help the patients involved.